A new species of Enderleina Jewett (Plecoptera, Perlidae) from Amazonas State, Brazil - Hamada, N.; Silva, J. O.; Pedroza, M. K. (Zootaxa, 2016)
Enderleina Jewett, 1960 is one of the least-known Perlidae genera in northern South America, including six species. During an aquatic insect survey of the northern portion of Amazonas State, Brazil, we collected a male Enderleina with a distinct pronotum pattern and genitalic morphology. The objectives of this study are to describe a new species of Enderleina based on male morphology. The new species can be distinguished from all other Enderleina species in the male by the presence of a paired thin dark band on the mesal region of pronotum and by the structure of the penial armature.